A Radar-Based System for Detection of Human Fall Utilizing Analog Hardware Architectures of Decision Tree Model - Vassilis Alimisis; Dimitrios G. Arnaoutoglou; Emmanouil Anastasios Serlis; Argyro Kamperi; Konstantinos Metaxas; George A. Kyriacou; Paul P. Sotiriadis (IEEE Open Journal of Circuits and Systems)
A fall-detection system was implemented utilizing a 2.45 GHz continuous wave radar along with power-efficient and fully-analog integrated classifier architectures. The Power Burst Curve and the effective acceleration were derived from the short time Fourier transform, and then processed by the analog classifier. The proposed classifier architectures are based on different approximations of the Decision tree classification model. The architectures consist of three main building blocks: sigmoid function circuit, analog multiplier and an argmax operator circuit. To assess the hardware design, a thorough analysis is performed, comparing it to commonly used analog classifiers while exploiting the extracted data. The architectures were trained using Python and were compared to software-based classifiers. The circuit designs were executed using TSMC’s 90 nm CMOS process technology and the Cadence IC Suite was employed for tasks including design, schematic implementation, and post-layout simulations.